Integrating adaptation practice in assessments of climate change science: The case of IPCC Working Group II reports. Issue 135 (September 2022) - Howarth, Candice; Viner, David
Abstract: The delivery of effective climate adaptation on the ground requires that the (climate adaptation) practitioner community be better incorporated into the process of producing, gathering and synthesizing evidence on adaptation as part of the Intergovernmental Panel on Climate Change (IPCC) process. This is not a recent issue and the co-production of knowledge, that goes beyond the traditional realms of 'science speaks to power', can only fully inform adequate and robust adaptation if it incorporates more practitioners, end-users, and those working at the interface of science, policy and practice. Through a high-level analysis of authors of the IPCC's Working Group II reports and special reports of AR6, we explore the evolution of representation of practitioners in IPCC WGII author teams from AR5 to AR6 and we find that practitioner representation has increased in AR6, however this remains low. We discuss how this low representation can affect readership and the potential to inform climate adaptation practice. As the IPCC evolves and reflects on its own practices, we seek to inform this process by providing further reflection on how the IPCC outputs can continue to be policy-relevant and maintain neutrality while ensuring accesibility and usability by climate adaptation practitioners. Highlights: Practitioner representation in IPCC WGII author teams remains low. Adaptation practitioners provide invaluable knowledge on adaptation best practice. Increased practitioners participation can help incorporate different perspectives. The IPCC must prioritise diversity in authorship teams to inform climate action.